Metabolic changes, agronomic performance, and quality of seeds in soybean with the pat gene after application of glufosinate - Albrecht, Alfredo Junior P.; Brito, Ivana Paula F. S. de [UNESP]; Albrecht, Leandro P.; Silva, Andre Felipe M.; Matos, Ana Karollyna A. de [UNESP]; Carbonari, Caio Antonio [UNESP]; Velini, Edivaldo D. [UNESP] (Cambridge Univ Press, 2020)
The transgenic Liberty Link((R)) (LL) soybean is tolerant to glufosinate, conferred by the enzyme phosphinothricin acetyltransferase (PAT), which is encoded by the pat gene from Streptomyces viridochromogenes. Because symptoms of injury can be observed in soybean [Glycine max (L.) Merr.] plants in some situations, this study evaluated the effects of rates of glufosinate on agronomic performance; quality of LL soybean seeds; and the ammonia, glufosinate, and N-acetyl-l-glufosinate concentration (NAG) in soybeans with and without the pat gene after application of increasing glufosinate rates. Field and greenhouse experiments were conducted; the first evaluated the selectivity of glufosinate in LL soybeans, and the second evaluated the metabolic changes in soybeans with (LL) and without (RR2) the pat gene, after application of glufosinate. For fieldwork, application of glufosinate at rates up to four times the maximum recommended caused initial injury symptoms (up to 38.5%) in LL soybean plants. However, no negative effect was found on seed quality and agronomic performance of LL plants, including yield. This shows the selectivity of glufosinate promoted by pat gene insertion for application in POST (V4), in LL soybean. For the greenhouse experiment, it was concluded that the LL soybean plants presented high glufosinate metabolism, lower ammonia concentration, and no reduction in dry matter, in comparison with RR2 soybean, after application of high rates of glufosinate.
Keywords: Crop injury; glufosinate-tolerant soybean; glutamine synthetase; N-acetyl-l-glufosinate; selectivity